Bantuan Hukum "Pro Bono Publico" sebagai Alternatif dalam Pemenuhan Hak Memperoleh Keadilan di Provinsi Jawa Timur - Tony Yuri Rahmanto (Jurnal HAM, 2015)
Law enforcement in Indonesia is more complicated and not easy. During the process under the rule of authoritarian government where the freedom to obtain equality before the law deliberately systematically restricted. Since the Law on Legal Aid was passed by the House of Representatives in 2011, a variety of hope began to appear for the sake of the establishment of a legal aid system that can be accessed by all groups of society, especially people can't afford (poor). But along the way, there are still many weaknesses and needs significant improvement. Therefore the problem is how the implementation of the provision of free legal aid (pro bono publico) by the local government for the poor society in East Java province; and how the coordination between the Provincial Government of the East Java with Regional Office of the Ministry of Justice and Human Rights in East Java as legal aid providers in the area. This research method using descriptive qualitative approach. Then conducted a qualitative analysis of the substance and research context to the aspects of Human Rights. The practice of providing legal aid to the poor society in East Java province is still experiencing problems, such as lack of socialization related to the provision of legal aid to the poor society, inadequate number of Legal Aid organization in making the provision of legal aid, the amount of the cost of legal aid has not been sufficient in the process in the trial, as well as administrative requirements related Certificate Disadvantaged (SKTM) are abused by some unscrupulous and not according to their distribution.